2019
DOI: 10.15252/embj.2019102147
|View full text |Cite
|
Sign up to set email alerts
|

SLC 1A3 contributes to L‐asparaginase resistance in solid tumors

Abstract: L‐asparaginase (ASNase) serves as an effective drug for adolescent acute lymphoblastic leukemia. However, many clinical trials indicated severe ASNase toxicity in patients with solid tumors, with resistant mechanisms not well understood. Here, we took a functional genetic approach and identified SLC1A3 as a novel contributor to ASNase resistance in cancer cells. In combination with ASNase, SLC1A3 inhibition caused cell cycle arrest or apoptosis, and myriads of metabolic vulnerabilities in tricarboxylic acid (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…However, although, intuitively, ASNS induction has been correlated with resistance to ASNase, it has been known for many years that ASNase-resistant ALL cells present a complex phenotype. Indeed, if ASNS overexpression is sufficient to induce the ASNase-resistant phenotype in specific ALL cell models (22), adequate availability of the ASNS substrates Gln and aspartate (Asp) requires multiple adaptation mechanisms (26,27) (Figure 1).…”
Section: Low Asns Expression In Acute Lymphoblastic Leukemia: Old Obsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, although, intuitively, ASNS induction has been correlated with resistance to ASNase, it has been known for many years that ASNase-resistant ALL cells present a complex phenotype. Indeed, if ASNS overexpression is sufficient to induce the ASNase-resistant phenotype in specific ALL cell models (22), adequate availability of the ASNS substrates Gln and aspartate (Asp) requires multiple adaptation mechanisms (26,27) (Figure 1).…”
Section: Low Asns Expression In Acute Lymphoblastic Leukemia: Old Obsmentioning
confidence: 99%
“…Central panel, ASNS induction and increase in GS protein expression are not able to rescue ASNase-induced apoptotis due to poor availability of their substrates Asp and Glu. Lower panel, the overexpression of EAAT1 or EAAT3 anionic amino acid transporters provides Glu (for the synthesis of Gln, through Glutamine Syntethase) and Asp (27). Both Gln and Asp are needed for Asn synthesis via ASNS and for an effective cell rescue.…”
Section: Low Asns Expression In Acute Lymphoblastic Leukemia: Old Obsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar processes are likely to occur in other cancers. Indeed, recently EAAT1 has been implicated in supporting proliferation in several cancer cell lines representing solid cancers [62,63]. Both studies showed a main role for EAAT1 in the uptake of aspartate from the medium, especially under conditions of glutamine deprivation or asparaginase treatment.…”
Section: Discussionmentioning
confidence: 99%